2019
DOI: 10.1002/adfm.201807893
|View full text |Cite
|
Sign up to set email alerts
|

Van der Waals Bipolar Junction Transistor Using Vertically Stacked Two‐Dimensional Atomic Crystals

Abstract: The majority of microelectronic devices rely on a p-n junction. The process of making such a junction is complicated, and it is difficult to make layers that form a junction with an atomic thickness. In this study, bipolar junctions are made by using 2D atomic crystalline layers and even a single layer in which 2D layers adhere together to form a heterostructure via van der Waals forces. A vertical 2D bipolar junction transistor (V2D-BJT) is studied for the first time. It uses an MoS 2 /WSe 2 /MoS 2 heterostru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 52 publications
0
54
0
Order By: Relevance
“…The proposed approach exhibits promise for large-scale integrated circuits based on 2D heterostructures. transistors (BJT), [15][16][17][18] logic inverters, and memories, [3,5,[19][20][21] showing great potential in the future nanoelectronics. [6,[22][23][24][25][26][27] However, most of the reported studies can only achieve a single function on the same heterostructure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed approach exhibits promise for large-scale integrated circuits based on 2D heterostructures. transistors (BJT), [15][16][17][18] logic inverters, and memories, [3,5,[19][20][21] showing great potential in the future nanoelectronics. [6,[22][23][24][25][26][27] However, most of the reported studies can only achieve a single function on the same heterostructure.…”
Section: Introductionmentioning
confidence: 99%
“…BJT, which is the fundamental building block of modern electronic devices, is used for signal gains, [38,39] including NPNtype and PNP-type. Although BJTs based on 2D van der Waals heterostructures have exhibited superior electrical amplification performance in the literature, [15][16][17][18]34,37] these structures are fabricated through an intricate manufacturing process, which restricts the development of 2D materials BJTs. Moreover, the influence of key parameters on device performance, such as carrier concentration and base width, has never been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…[178] Analyte molecules in the semiconductor layer act as the trapping site; therefore, the charge carrier density and molecular properties of the semiconductors are therefore influenced, leading to the change of the charge-transfer characteristic, i.e., reducing the semiconductor conductivity. [179] Kang et al [71] fabricated an organic FET-based chemical sensor with improved crystallinity using an organic heterointerface and successfully controlled the morphology of an organic thin film. For the dielectric layer, m-bis(triphenylsilyl) benzene (TSB3) was thermally vaporized on the substrate with a low glass transition temperature.…”
Section: F-fet Sensors For Detecting Environment Conditionsmentioning
confidence: 99%
“…[ 178 ] Analyte molecules in the semiconductor layer act as the trapping site; therefore, the charge carrier density and molecular properties of the semiconductors are therefore influenced, leading to the change of the charge‐transfer characteristic, i.e., reducing the semiconductor conductivity. [ 179 ]…”
Section: Chemical and Biological Sensors Based On F‐fetsmentioning
confidence: 99%
“…14 Multifunctional p-n diodes, 25,26 ultrasensitive photodetectors, 27,28 high-performance memories, 29,30 light-emitting diodes, 31 and bipolar junction transistors 32 have been fabricated from these materials, showing their potential application in future nanoelectronics. Although several studies on BJTs based on 2D van der Waals heterostructures can be found in the literature, [33][34][35][36][37][38] these structures have an intricate growth procedure 33,34 and tedious multistep transfer process, [35][36][37] making them difficult to fabricate. More importantly, one of the critical factors that inuences BJT performance is the difference in the major carrier concentration between the emitter and collector, which has never been explored until now.…”
Section: Introductionmentioning
confidence: 99%